THE EFFECT OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN THE MANUFACTURING INDUSTRY - Tionom Nainggolan; Tibrani; Rona Tanjung; Hanafi Siregar (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study aims to examine the influence of leadership, organizational culture, and work stress on employee performance in a manufacturing company. In the context of global competition, manufacturing companies face significant challenges in maintaining and improving employee performance. Inspiring and motivating transformational leadership, a positive organizational culture, and high work motivation are key factors in achieving these goals. This study used a quantitative approach with a survey method of 200 employees in a manufacturing company in Indonesia. The results show that these three variables have a positive and significant influence on employee performance. These findings provide practical implications for managers and company leaders in developing strategies to improve employee performance and achieve long-term success.